Production of microalgal biochar and reducing sugar using wet torrefaction with microwave-assisted heating and acid hydrolysis pretreatment - Yu, Kai Ling; Chen, Wei Hsin; Sheen, Herng Kuang; Chang, Jo-Shu; Lin, Chih Sheng; Ong, Hwai Chyuan; Show, Pau Loke; Ng, Eng Poh; Ling, Tau Chuan (Elsevier, 2020)
This study employed the microwave-assisted acid hydrolysis pretreatment using wet torrefaction on two indigenous microalgae, Chlorella vulgaris ESP-31 and Chlorella sp. GD with different biomass composition to investigate the yields of solid biochar and total reducing sugar in the liquid hydrolysate. Operating conditions at low temperatures (160, 170 °C) with short holding time (5, 10 min) under several concentrations of diluted acid medium (0, 0.1 and 0.2 M) were carried out to investigate the torrefaction severity effects towards the properties of the solid and liquid products. The highest biochar yields of 54.5% and 74.6% are obtained from C. vulgaris ESP-31 and Chlorella sp. GD, respectively under the wet torrefaction conditions with an improvement in the properties for fuel and value-added environmental application. The highest total reducing sugar concentration of 98.11 g/L and 12.08 g/L are obtained in C. vulgaris ESP-31 and Chlorella sp. GD liquid hydrolysates, respectively after acid hydrolysis pretreatment. With the co-production of high total reducing sugar in the liquid hydrolysate that can be utilized for bioethanol production and solid biochar as another value-added product, the acid hydrolysis pretreatment using wet torrefaction can be one of the conversion technologies towards the application of renewable energy production. © 2020 Elsevier Ltd